Two Uncommon Cases of Pediatric Transethmoidal–Transnasal Encephaloceles with a Review of Literature - Acharya, Abhijit; Senapati, Satya Bhusan; Panigrahi, Souvagya; Deo, Rama Chandra; Mahapatra, A. K. (Indian Journal of Neurosurgery, 2024)
Encephaloceles are defined as the herniation of brain matter beyond the confines of the skull bone through a defect on the cranium or face. The encephaloceles are classified into different categories as per onset as congenital or traumatic, as per contents as meningocele, meningoencephalocele, and hydromeningoencephalocele, and as per anatomical location into frontoethmoid, basal, occipital, and cranial vault. Transethmoidal encephalocele is a rare type of encephalocele with a very few patients reported in the literature to date. We are presenting two cases of transethmoidal–transnasal encephalocele in the pediatric age group with one being congenital and other traumatic in onset. The first child presented with a mass visible inside the nasal cavity since birth with nasal obstruction. The second child presented with a history of trauma 5 years back followed by occasional cerebrospinal fluid leak, fever, and nasal stuffiness. Both patients underwent craniotomy and excision of the encephalocele with repair of the defect in the cribriform plate. These two uncommon cases highlight the different onsets of the disease successfully managed surgically.
Keywords: Encephaloceles; cranial defects; image-guided neurosurgery; neurosurgery